Influence of the mRNA initial region on protein production: a case study using recombinant detoxified pneumolysin as a model - Fusco, Filipe; Pires, Manuella Cazelato; Lopes, Alexandre Paulo Yague; Alves, Vítor dos Santos; Gonçalves, Viviane Maimoni (Frontiers in Bioengineering and Biotechnology, 2024)
Recombinant proteins are of great importance in modern society, mostly as biopharmaceutical products. However, challenging and complex processes with low production yield are major drawbacks. Normally, the optimization to overcome these obstacles is focused on bioreactor and purification processes, and the biomolecular aspects are left behind, seen as less important. In this work, we present how 5' mRNA secondary structure region can be relevant for translation and, therefore, protein production. For this, Escherichia coli BL21(DE3) clones, producing recombinant detoxified pneumolysin (PdT) with and without N-terminal His-tag, were cultivated in 10 L bioreactors. Another version of pdt gene (version 2) with synonymous changes in the 5' end nucleotide sequence was also obtained. Protein production, plasmid stability, carbon sources and acetic acid were quantified during the cultures. Furthermore, in silico mRNA analyses were performed using TIsigner and RNAfold. The results showed that the His-tag presence at N-terminus generated a minimum 1.5-fold increase in target protein synthesis, which was explained by the in silico mRNA analyses that returned a mRNA secondary structure easier to translate and, therefore, higher protein production than without His-tag. The pdt gene version 2 showed lower 5' mRNA opening energy than version 1, allowing higher PdT production even without tag. This work reveals that simple mRNA analyses during heterologous gene design and production step can help to reach high recombinant protein titers in shorter time than using only traditional bioprocess optimization strategies.